Effects of different resistance training volumes on strength and power in team sport athletes - Naclerio, F.; Faigenbaum, A. D.; Larumbe-Zabala, E.; Perez-Bibao, T.; Kang, J.; Ratamess, N. A.; Triplett, N. T. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to compare the effects of 3 different volume of resistance training (RT) on maximum strength and average power in college team sport athletes with no previous RT experience. Thirty-two subjects (20 men and 12 women, age = 23.1 ± 1.57 years) were randomly divided into 4 groups: low volume (LV; n = 8), 1 set per exercise and 3 sets per muscle group; moderate volume (MV; n = 8), 2 sets per exercise and 6 sets per muscle group; high volume (HV; n = 8), 3 sets per exercise and 9 sets per muscle group; and a non-RT control group (n = 8). The 3 intervention groups were trained for 6 weeks thrice weekly after a nonperiodized RT program differentiated only by the volume. Before (T1) and after training (T2), 1 repetition maximum (1RM) and maximal average power (AP) produced on the bench press (BP), upright row (UR), and squat (SQ) were assessed by progressive resistance tests. One repetition maximum-BP and 1RM-UR increased significantly in the 3 interventions groups (p < 0.05), whereas only the HV group significantly improved 1RM-SQ (p < 0.01). The MV and HV groups increased AP-BP (p < 0.05), whereas only the LV group improved AP-SQ (p < 0.01). Moderate effect sizes (ES; >0.20 < 0.60) were observed for the 1RM-BP and 1RM-UR in the 3 training groups. High-volume group showed the larger ES for 1RM-BP (0.45), 1RM-UR (0.60), and 1RM-SQ (0.47), whereas the LV produced the higher ES for SQ-AP (0.53). During the initial adaptation period, a HV RT program seems to be a better strategy for improving strength, whereas during the season, an LV RT could be a reasonable option for maintaining strength and enhancing lower-body AP in team sport athletes.